Development of power electronics and control systems II - Tseng, King Jet. (2008)
A novel power factor and input current THD improvement scheme for a suppressed-link rectifier-inverter structure has been suggested and is verified to be functional over an extended converter operating range. A prototype of the converter has also been designed, built and tested.